Age-related differences in psychopathology within sex chromosome trisomies. - Roybal, Melissa R.; Liu, Siyuan; Larsen, Isabella G.; Wass, Anastasia; Schaffer, Lukas; Ajumobi, Tiffany; Whitman, Ethan T.; Warling, Allysa; Clasen, Liv; Blumenthal, Jonathan; Rau, Srishti; Raznahan, Armin (European Child & Adolescent Psychiatry, 2025)
Sex chromosome trisomies (SCTs) are a group of genetic disorders characterized by presence of a supernumerary sex chromosome, resulting in karyotypes other than XX or XY. These include XXX (Trisomy X), XXY (Klinefelter syndrome), and XYY (Jacobs syndrome). SCTs have been linked to increased risk for psychopathology; however, this relationship warrants additional research. Specifically, little is known regarding potential age-related variation in risk for psychopathology and how this may differ across karyotypes and subdomains of psychopathology. This has important implications for psychoeducation (e.g., informing carriers of the likelihood for varying manifestations with age), personalized care, and research into the mechanisms of pathophysiology. Thus, we used the Child Behavior Checklist (CBCL) to estimate age-related variation in psychopathology in a large cross-sectional sample of SCT carriers (n = 201) and euploidic controls (n = 304) spanning the age range of 5–18 years. We found that elevations of psychopathology in carriers were significantly associated with age in a manner that varied as a combined function of the karyotype and CBCL scale being considered. Post hoc tests revealed there is a uniquely pronounced age-associated increase in severity of social problems in the XYY karyotype, alongside a lack of statistical evidence for age-related variation in the severity of psychopathology for other CBCL domains and SCT karyotypes. Our findings are relevant for advancing the personalization of clinical assessment and monitoring in SCT carriers. They also highlight potential windows of dynamic risk emergence for closer clinical and biological study, as well as opportunities to provide intervention to mitigate future risk.